Microstructure and Performance Research on Ceramic-Enhanced Inconel 718 Matrix Composite Using Laser Additive Manufacturing - Qingtao Yang; Zewei Xu; Liangliang Li; Pengfei Li (Metals, 2023)
This article presents a 95% IN718 + 5% (75% Cr2O3 + TiO2) ceramic coating on the SS316L substrate surface with laser additives. The macro shape, phase, microstructure, interface, wear resistance and tensile resistance of metal base composite materials are analyzed. The results show that metal matrix composite (MMC) laminated composite materials have good microscopic hardness and wear resistance compared to single materials. Comparative analyses with single IN718 materials indicate that the laminated composite materials exhibit superior microscopic hardness and wear resistance. Additionally, the study reveals a positive correlation between material hardness and wear resistance, characterized by reduced wear coefficient and average abrasion with increased material hardness. The findings of this research offer a cost-effective and practical method for producing high-resistance coating layer composite materials.